A Puzzling Case of Biliary Stricture with Calcified Liver Nodules - VM, Leow; MS, Faizah; KF, Yang; MN, Hasnan; SS, Manisekar (IIUM Medical Journal Malaysia, 2013)
Tuberculous (TB) biliary stricture with calcified liver nodules rendering obstructive jaundice is a rare clinical phenomenon. Recently, we encountered a young patient with obstructive jaundice who was investigated in a general hospital. He was sent to our hospital for subsequent management after undergoing a series of investigations and biliary stenting. The radiological imagings performed revealed multiple calcified lesions in the liver with proximal bile duct strictures. Blood investigations, tumor markers and tuberculous work up were not remarkable. Subsequently, he underwent laparotomy and biliary reconstruction. Postoperatively, he was discharged well. Histopathological examination of the hepatoduodenal nodes showed chronic infections and granulomatous lymphadenitis, suspicious of a mycobacterium infection.